2017
DOI: 10.1155/2017/9425361
|View full text |Cite
|
Sign up to set email alerts
|

Exploring Polymer-Modified Concrete and Cementitious Coating with High-Durability for Roadside Structures in Xinjiang, China

Abstract: The concrete roadside structures in Xinjiang, China, such as roadside barriers, bridge rails, and drainage holes, are severely damaged by the coupled effect of seasonal freeze-thaw cycles and deicer salts. To solve the corrosion problems of roadside structures, polymermodified concrete was recommended for the future construction of roadside structures and polymer-modified cementitious coating was suggested for the protection of the current corroded ones. In this study, air-entraining agent and carboxylated sty… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
6
0
1

Year Published

2018
2018
2024
2024

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 10 publications
(7 citation statements)
references
References 19 publications
0
6
0
1
Order By: Relevance
“…The SME-PS protectant was applied by immerging the samples in the SME-PS blend for 6 h (dosage 1) and 24 h (dosage 2) ( 51 ). Moreover, the performance of concrete sealers—including polyurea, epoxy, long-chain/fluorinated silane, ACM&HG (spray coating for polyurea while brush coating for all the other sealers with a dosage of 4 m 2 /kg) ( 33 ), linseed oil, silane, siloxane (one-time brush coating with a dosage of 3.07 m 2 /L) ( 76 ), acrylate-copolymer-/acrylic-latex-modified cementitious coating (a controlled thickness of 3–5 mm) ( 126 ), and 40% silane-based water repellent (two-time brush coating with an interval of 6 h and a dosage of 6.9 m 2 /L) ( 127 )—in improving F/T durability of concrete samples is compared with that of SME-5%PS. Although bacteria have been used in repairing systems to improve the F/T resistance of concrete pavement ( 128 ) and used as surface deposition to improve the F/T resistance of limestone ( 129 ), there are few studies investigating the influence of biotic sealers on concrete.…”
Section: Comparative Evaluation Of Sme-ps Performance To Mitigate Con...mentioning
confidence: 99%
“…The SME-PS protectant was applied by immerging the samples in the SME-PS blend for 6 h (dosage 1) and 24 h (dosage 2) ( 51 ). Moreover, the performance of concrete sealers—including polyurea, epoxy, long-chain/fluorinated silane, ACM&HG (spray coating for polyurea while brush coating for all the other sealers with a dosage of 4 m 2 /kg) ( 33 ), linseed oil, silane, siloxane (one-time brush coating with a dosage of 3.07 m 2 /L) ( 76 ), acrylate-copolymer-/acrylic-latex-modified cementitious coating (a controlled thickness of 3–5 mm) ( 126 ), and 40% silane-based water repellent (two-time brush coating with an interval of 6 h and a dosage of 6.9 m 2 /L) ( 127 )—in improving F/T durability of concrete samples is compared with that of SME-5%PS. Although bacteria have been used in repairing systems to improve the F/T resistance of concrete pavement ( 128 ) and used as surface deposition to improve the F/T resistance of limestone ( 129 ), there are few studies investigating the influence of biotic sealers on concrete.…”
Section: Comparative Evaluation Of Sme-ps Performance To Mitigate Con...mentioning
confidence: 99%
“…Kompozytowe materiały cementowe KSB/cement znalazły szerokie zastosowanie w naprawach dróg i mostów (8,(13)(14)(15). Jednakże, podobnie jak w przypadku innych polimerów (16)(17)(18), dodatek KSB znacznie opóźnia proces hydratacji cementu.…”
Section: Wprowadzenieunclassified
“…In addition, the carbonation resistance, chloride ions permeability resistance and durability are improved as well (2,(10)(11)(12). SB/cement composite cementitious materials have been widely used in roads and bridges repairs (8,(13)(14)(15). However, similar to other polymers (16)(17)(18), the hydration process of cement is signifi cantly retarded in the addition of SB.…”
Section: Introductionmentioning
confidence: 99%
“…Recently, several polymers that are soluble in water and polymeric particles that are distributed in water (latexes) have been introduced in mortars and to concretes increase their fluidity (Anagnostopoulos and Dimitriadi, 2021). One of the best performance was achieved by "C6"(an acrylic-modified cementations coating compound), which was sprayed to a corroded highway wayside barrier in Xinjiang as part of a project to safeguard it, and three years of monitoring revealed that the coating functioned well in the field without visible delamination or cracking (Guo et al, 2017). In another study, polymer has been successfully employed to improve the properties of concrete mixtures (Aggarwa et al, 2007).…”
Section: Introductionmentioning
confidence: 99%